Psychological-pedagogical conditions in forming relationships in a modern family - Меркулова, Анна; Нагымжанова, Каракат; Власова, Нина (Pedagogy and Psychology, 2020)
The article discusses the issues of psychological and pedagogical conditions for the formation of relationships between family members, as one of the key areas in the family education of children realizing the ability and desire to learn, as the basis of professional training of future psychologists. An analysis is made of the conditions for the development of communication between family members from the perspective of a personal-activity approach. The basic conditions for the formation of positive relationships in the family and modern approaches to the use of communication tools to enhance positive emotions are revealed. The most significant communication situations arising in the learning process are considered. The article also notes methods aimed at developing the skills of positive interaction between family members and increasing the socialization of children in society. Recommendations are used for parents to establish positive relationships and how to describe from a positive point of view, instructions to make a child better, and easily resolve family conflicts. Recommendations are given to move the child away from the computer and make his life more diverse and fun using various activities where it is necessary to make efforts to obtain a result.